Organic compound composition in soil and sediments collected in Jackson, Mississippi. Issue 7 (6th June 2016) - Gołębiowski, Marek; Stepnowski, Piotr; Hemmingway, Tometrick; Leszczyńska, Danuta
ABSTRACT: The aim of our study was to identify organic pollutants found in soil and sediment samples collected within the Jackson, MS metropolitan area. The chemical characterization of the organic compound fractions in soil and sediment samples was carried out by separating the organic fraction using column chromatography (CC) and quantitatively analyzing the polycyclic aromatic hydrocarbons (PAHs), n-alkanes and other organic compounds using gas chromatography–electron impact mass spectrometry (GC–MS). Fifty-six compounds were identified and quantified in the soil samples and 33 compounds were identified and quantified in the sediment samples. The PAHs, n-alkanes and other organic compound profiles in the soil and sediment samples were compared. The percentage contents of the organic compounds in the soil samples were very diverse (from traces to 12.44 ± 1.47%). The compounds present in the highest concentrations were n-alkanes: n-C31 (12.44 ± 1.47%), n-C29 (11.64 ± 1.21%), and n-C33 (8.95 ± 1.08%). The components occurring in smaller quantities (from 1% to 5%) were 2 PAHs (fluoranthene 1.28 ± 0.25%, pyrene 1.16 ± 0.20%), 10 n-alkanes from n-C21 (1.25 ± 0.29%) to n-C32 (2.67 ± 0.52%) and 11 other compounds (e.g., 2-pentanol, 4-methyl (3.33 ± 0.44%), benzyl butyl phthalate (4.25 ± 0.59%), benzenedicarboxylic acid (1.14 ± 0.08%), ethane, 1, 1-diethoxy (3.15 ± 0.41) and hexadecanoic acid (2.52 ± 0.34). The soil samples also contained 30 compounds present in concentrations <1% (e.g., anthracene (0.13 ± 0.04%), n-C20 (0.84 ± 0.21%) and acetic acid (0.12 ± 0.04%). The compounds present in the highest concentrations in the sediment samples were PAHs: pyrene (7.73 ± 1.15%) and fluoranthene (6.23 ± 1.07%) and n-alkanes: n-C31 (6.74 ± 1.21%), n-C29 (6.65 ± 0.98%) and n-C27 (6.13 ± 1.09%). The remaining organic compounds were present in smaller quantities (< 5%).